2016
DOI: 10.1371/journal.pone.0157260
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Task Demands on Fixation-Related Brain Potentials during Guided Search

Abstract: Recording synchronous data from EEG and eye-tracking provides a unique methodological approach for measuring the sensory and cognitive processes of overt visual search. Using this approach we obtained fixation related potentials (FRPs) during a guided visual search task specifically focusing on the lambda and P3 components. An outstanding question is whether the lambda and P3 FRP components are influenced by concurrent task demands. We addressed this question by obtaining simultaneous eye-movement and electroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…Preferably, this would be in an environment with minimal noise affecting the brain and eye signals, but also situations where the signal is strong—e.g., low workload scenarios are beneficial when exploiting the P300 signal to distinguish between targets and non-targets (current study, Thurlings et al, 2013; Ries et al, 2016). An example that may capture these elements is robust image triage.…”
Section: Discussionmentioning
confidence: 89%
“…Preferably, this would be in an environment with minimal noise affecting the brain and eye signals, but also situations where the signal is strong—e.g., low workload scenarios are beneficial when exploiting the P300 signal to distinguish between targets and non-targets (current study, Thurlings et al, 2013; Ries et al, 2016). An example that may capture these elements is robust image triage.…”
Section: Discussionmentioning
confidence: 89%
“…The results showed decreased P300 amplitude with increased working memory load for the incongruent flanker stimuli. P300 latency is also affected by task demands, as demonstrated in a recent study by Ries et al [35], which showed that target response latency significantly increased as a function of auditory working memory load.…”
Section: Task Demandsmentioning
confidence: 79%
“…Of course, the decision to reject the Null Hypothesis (i.e that target amplitudes are the same in both conditions) is a function of several factors, including significance threshold and multiple-comparison corrections. In the original paper [35], the authors did not report a significant difference in amplitudes after performing a multiplecomparisons correction. Use of CNN outputs would have affected this result due to the enhanced SNR of the CNN method.…”
Section: Noise Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Dimigen, Sommer, Hohlfeld, Jacobs, & Kliegl, 2011). Most studies so far have studied the EEG in the time domain, that is, fixation-related potentials (FRPs), for example in reading research (Dimigen, et al, 2011;Frey, Lemaire, Vercueil, & Guérin-Dugué, 2018;Henderson, Luke, Schmidt, & Richards, 2013;Hutzler et al, 2007;Kliegl, Dambacher, Dimigen, & Sommer, 2014;Kornrumpf, Dimigen, & Sommer, 2017;Kornrumpf, Niefind, Sommer, & Dimigen, 2016;Léger et al, 2014;Weiss, Knakker, & Vidnyánszky, 2016), natural scene perception (Giannini, Alexander, Nikolaev, & van Leeuwen, 2018;Simola, Le Fevre, Torniainen, & Baccino, 2015;Simola, Torniainen, Moisala, Kivikangas, & Krause, 2013), visual search (Brouwer, Hogervorst, Oudejans, Ries, & Touryan, 2017;Kamienkowski, Ison, Quiroga, & Sigman, 2012;Kaunitz et al, 2014;Ries, Touryan, Ahrens, & Connolly, 2016;Winslow et al, 2010), decision making (Frey et al, 2013), and human-computer interaction (Léger et al, 2014). Despite methodological challenges (see below) these studies concurrently report FRP-effects comparable to classical ERP-effects (e.g., N400-like effects for word predictability; Dimigen et al, 2011), thus validating the feasibility and meaningfulness of fixation-related EEG data analyses.…”
Section: Fixation-related Eeg Data Analysismentioning
confidence: 99%